Sanksi Hukum Tindak Pidana Kecelakaan Lalu Lintas di Indonesia - Yosbenhard , Andreas; Rahmat, Dinding (Neolectura, 2025)
Indonesia, as a state based on law, aims to achieve public welfare, including through a safe and orderly traffic and road transportation system. Roads, being essential infrastructure, require comprehensive regulations to ensure safety and security. Traffic accidents are classified as criminal offenses under Article 310 paragraphs (2), (3), and (4) of Law No. 22 of 2009. These offenses are considered crimes against life and bodily integrity. This study employs a normative juridical method to examine the legal framework and implementation strategy of electronic traffic law enforcement (ETLE) to optimize traffic law enforcement across Indonesia. The findings show that traffic accident crimes are regulated under Articles 103, 338, and 359 of the Criminal Code (KUHP), and Articles 311, 314, and 235 of Law No. 22 of 2009. In addition to criminal penalties, civil liability in the form of compensation may also apply. Negligent drivers causing fatalities may face imprisonment of up to 6 years or a fine of Rp12,000,000. The study suggests the need for new, stricter legislation regarding traffic crimes through updates to the existing laws, Criminal Code, government regulations, and Ministry decrees to improve enforcement